In vivo antileishmanial activity and histopathological evaluation in Leishmania infantum infected hamsters after treatment with a furoxan derivative - de Almeida, Letícia [UNESP]; Passalacqua, Thaís Gaban [UNESP]; Dutra, Luiz Antonio [UNESP]; Fonseca, Jéssica N. Varonez da [UNESP]; Nascimento, Rhayanne F. Queiroz [UNESP]; Imamura, Kely Braga [UNESP]; de Andrade, Cleverton Roberto [UNESP]; dos Santos, Jean Leandro [UNESP]; Graminha, Márcia A.S. [UNESP] (Elsevier, 2017)
N-oxide derivatives compounds such as furoxan and benzofuroxan are promising scaffolds for designing of new antileishmanial drugs. A series of furoxan (1,2,5-oxadiazole 2-N-oxide) (compounds 4a-b, and 14a-f) and benzofuroxan (benzo[c][1,2,5]oxadiazole1-N-oxide) (compounds 8a-c) derivatives were evaluated against in vitro cultured L. infantum promastigotes and amastigotes. The compounds exhibited activity against promastigote and intracellular amastigote forms with EC50 values ranging from 2.9 to 71.2 μM and 2.1 to 18.2 μM, respectively. The most promising compound, 14e, showed good antileishmanial activity (EC50 = 3.1 μM) against intracellular amastigote forms of L. infantum with a selectivity index, based on murine macrophages (SI = 66.4), almost 3-times superior to that presented by the standard drug amphotericin B (AmpB). The efficacy of 14e to eliminate the parasites in vivo was also demonstrated. Treatment of L. infantum-infected hamsters with compound 14e at 3.0 mg/Kg/day led to a meaningful reduction of parasite load in spleen (49.9%) and liver (54.2%), respectively; these data were corroborated by histopathological analysis, which also revealed reduction in the number of inflammatory cells in the liver of the treated animals. Moreover, histological analysis of the spleen and kidney of treated animals did not reveal alterations suggestive of toxic effects. The parasite load reduction might be related to NO production, since this molecule is a NO-donor. We observed neither side effects nor elevation of hepatic/renal biomarker levels in the plasma. The data herein presented suggest that the compound should be considered in the development of new drugs for treatment of visceral leishmaniasis.
Keywords: Furoxan derivatives; In vivo antileishmanial activity; L. infantum; NO-donor; Semi-quantitative histopathological analysis; Visceral leishmaniasis